Hello all, I need the answer to the following equation, I'd very much appreciate it!

find A)f o g and b) g o f given F(x) = square root of (x+4) and g(x) = x^2 - 4

if you could give me the answer and briefly go over the steps in finding the equation, i'd be glad!

Swishh

do you understand what fog and gof means....it is easy...just replace in the place of x the other function
ie. gof(x): get g(x) as function and instead of x replace (substitute) the whole f(x) as it is......same for fog revise the chaper of the composite functions pls.

MINOAS

If, for example, $\displaystyle f(x)= 3x^2- x+ 6$ and $\displaystyle g(x)= x^3+ 2x$ then fog(x)= f(x^3+ 2x)= 3(x^3+ 2x)^2- (x^3+ 2x)+ 6[/tex] and $\displaystyle gof(x)= g(3x^2- x+ 6)= (3x^2- x+ 6)^3+ 2(3x^2- x+ 6)$.

bump. are both f o g and g o f = to x?

Originally Posted by swishh
are both f o g and g o f = to x?
You must realize that $\displaystyle \sqrt{x^2}=|x|\ne x~.$

Originally Posted by Plato
You must realize that $\displaystyle \sqrt{x^2}=|x|\ne x~.$
is this for f o g or g o f?

is the answer for f o g and g o f both x, or is it absolute value of x?

Originally Posted by swishh
is this for f o g or g o f?
is the answer for f o g and g o f both x, or is it absolute value of x?
$\displaystyle f(g(-3))=~?~~\&~~g(f(-3))=~?$